2018
DOI: 10.1371/journal.pone.0192536
|View full text |Cite|
|
Sign up to set email alerts
|

Differential desulfurization of dibenzothiophene by newly identified MTCC strains: Influence of Operon Array

Abstract: Since the sulfur specific cleavage is vital for the organic sulfur removal from fossil fuel, we explored potential bacterial strains of MTCC (Microbial Type Culture Collection) to desulfurize the Dibenzothiophene (DBT) through C-S bond cleavage (4-S pathway). MTCC strains Rhodococcus rhodochrous (3552), Arthrobacter sulfureus (3332), Gordonia rubropertincta (289), and Rhodococcus erythropolis (3951) capable of growing in 0.5 mM DBT were examined for their desulfurization ability. The presence of dsz genes as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
0
20
1
1
Order By: Relevance
“…It entails the use of competent microorganisms to selectively remove sulphur from organosulphur hydrocarbons to complement HDS without degrading its carbon skeleton. Some of these organisms are Rhodococcus , Lysinibacillus , Pseudomonas , Sphingomonas , Bacillus , Gordonia, Acinetobacter , Arthrobacter, Mycobacterium , Klebsiella, Caldariomyces Paenibacillus , and Enterobacter [79,80,81]. The availability of these sulphur-aromatic compounds to the microorganisms is one of the most challenging factors in the biodesulphurization process.…”
Section: Application Of Biosurfactants In the Petroleum Industrymentioning
confidence: 99%
“…It entails the use of competent microorganisms to selectively remove sulphur from organosulphur hydrocarbons to complement HDS without degrading its carbon skeleton. Some of these organisms are Rhodococcus , Lysinibacillus , Pseudomonas , Sphingomonas , Bacillus , Gordonia, Acinetobacter , Arthrobacter, Mycobacterium , Klebsiella, Caldariomyces Paenibacillus , and Enterobacter [79,80,81]. The availability of these sulphur-aromatic compounds to the microorganisms is one of the most challenging factors in the biodesulphurization process.…”
Section: Application Of Biosurfactants In the Petroleum Industrymentioning
confidence: 99%
“…HS126-4 N 95 % 2 0,2 mM [ 13 ] Gordonia alkanivorans 135 45 % 6 0,2 mM This study Gordonia sp. ZD-7 44 % 1 0.2 mM [ 34 ] Gordonia amicalis 6-1 98 % 15 0,1 mM [ 19 ] …”
Section: Discussionunclassified
“…The Gordonia strains are known to be capable of desulfurization of dibenzothiophene (DBT) with the formation of 2-hydroxybiphenyl (2-HBP), the final product of the 4S pathway [ [32] , [33] , [34] , [35] , 14 ]. In the works presented in Table 3 , the authors observed the maximum accumulation of this metabolite by the time of complete depletion of DBT in the system and entering the stationary growth phase by the culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It entails the use of competent microorganisms to selectively remove sulphur from organosulphur hydrocarbons to complement HDS without degrading its carbon skeleton. Some of these organisms are Rhodococcus, Lysinibacillus, Pseudomonas, Sphingomonas, Bacillus, Gordonia, Acinetobacter, Arthrobacter, Mycobacterium, Klebsiella, Caldariomyces Paenibacillus, and Enterobacter [79][80][81]. The availability of these sulphur-aromatic compounds to the microorganisms is one of the most challenging factors in the biodesulphurisation process.…”
Section: Biosurfactants In Biodesulphurizationmentioning
confidence: 99%